THE RELATIONSHIP BETWEEN PARENTING STYLES AND THE COGNITIVE DEVELOPMENT OF PRESCHOOL CHILDREN AT MATHLA'UL ANWAR KINDERGARTEN, BUARANJATI - Shofia Milla Hanifa; Alif Nurul Rosyidah; Osep Yasier Almunsiri (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: It is estimated that more than 200 million children under the age of five worldwide do not reach optimal cognitive development, with the majority living in Asia. Cognitive development in preschool-aged children is a process through which children develop the ability to think, remember, and understand their surroundings. This development is influenced by various factors, one of which is the environment—particularly parenting style. Parents play a crucial role in supporting the cognitive, physical, language, social, emotional, religious, moral,and artistic development of their children. Objective: To determine the relationship between parenting style and cognitive development of preschool-aged children at Mathla’ul Anwar Buaranjati Kindergarten. Methods: This research is a quantitative study with a cross-sectional approach. A total of 85 respondents were selected using purposive sampling. The instrument used was an ordinal-scalequestionnaire.Results: The Chi-Square test showed a p-value of 0.044 (< 0.05), indicating a significant relationship between parenting style and cognitive development in preschool-aged children at Mathla’ul Anwar BuaranjatiKindergarten.Conclusion: There is a significant relationship between parenting style and the cognitive development of preschool-aged children at Mathla’ul Anwar Buaranjati Kindergarten